2019
DOI: 10.1021/acssuschemeng.9b06194
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Imidazolium-Based Ionic Liquids as Refolding Additives for Urea-Induced Denatured Serum Albumins

Abstract: One of the major challenges in protein stability is that proteins can easily unfold in the presence of denaturants like urea, which alters the native structure of proteins. There are numerous studies in which ionic liquids (ILs) act as promising biocompatible solvents (Bio-IL) for biomolecules. In this context, we present the refolding ability of biocompatible imidazolium-based ILs, 1-ethyl 3-methyl imidazolium ethyl sulfate [Emim]­[ESO4] (IL-1) and 1-ethyl 3-methyl imidazolium chloride [Emim]­[Cl] (IL-2) agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…49 Furthermore, our earlier research reported the usability of a novel mixture of macromolecular crowders+IL for enhanced stability and activity of cytochrome c as compared to an IL and crowding agents alone. 47 Recently, Sindhu et al 50 reported imidazolium ethyl sulfate ([Emim]-[ESO4]) and 1-ethyl 3-methyl imidazolium chloride ([Emim]-[Cl]) as exceptional refolding agents for urea denatured serum albumins. However, the same ILs were found to destabilize the protein structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…49 Furthermore, our earlier research reported the usability of a novel mixture of macromolecular crowders+IL for enhanced stability and activity of cytochrome c as compared to an IL and crowding agents alone. 47 Recently, Sindhu et al 50 reported imidazolium ethyl sulfate ([Emim]-[ESO4]) and 1-ethyl 3-methyl imidazolium chloride ([Emim]-[Cl]) as exceptional refolding agents for urea denatured serum albumins. However, the same ILs were found to destabilize the protein structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1−5 Recently, many researchers have demonstrated that the addition of ionic liquids (ILs) to enzymes can improve the enzymatic activity and stability. 6,7 In 2019, Paẗzold et al 9 explained about deep eutectic solvents (DESs) as alternatives to ILs due to the lack of biodegradability, toxicity, lower sustainability, complexity in preparation, and high cost of ILs. Zhang et al 10 introduced DESs as emerging cosolvents to replace the anciently used ILs because of recyclability and availability of DESs compared to ILs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Enzymes are the biocatalysts that perform various biochemical transformations and industrial processes. , However, extreme processing conditions and the inherent instability of enzymes confines their potential applications. Addition of cosolvent is a simple and efficient method to improve the stability and reusability of enzymes against multiple stresses like high temperatures, pH, and nonaqueous solvents. Recently, many researchers have demonstrated that the addition of ionic liquids (ILs) to enzymes can improve the enzymatic activity and stability. , In 2019, Pätzold et al explained about deep eutectic solvents (DESs) as alternatives to ILs due to the lack of biodegradability, toxicity, lower sustainability, complexity in preparation, and high cost of ILs. Zhang et al introduced DESs as emerging cosolvents to replace the anciently used ILs because of recyclability and availability of DESs compared to ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Figures and show the specific binding of cholinium, acetate, dihydrogen phosphate, and dihydrogen citrate ions with F ab and F c fragments of IgG through molecular docking. However, the docking results for chloride could not be displayed as the Cl anion does not form a H-bond with the protein molecules Figures c,d and c,d show that hydrophobic interactions in the case of dihydrogen citrate and dihydrogen phosphate are higher with three amino acid residues of F ab , whereas three amino acid residues of F c fragments show hydrophobic interactions with dihydrogen phosphate, which has also been seen in the FT-IR studies.…”
Section: Resultsmentioning
confidence: 86%